PENGEMBANGAN BUDIDAYA CUMI-CUMI (Urotheutis chinensis) DI PERAIRAN TUING PULAU BANGKA PROVINSI KEPULAUAN BANGKA BELITUNG - Dwi Febrianti; Indra Ambalika Syari; Ahmad Fahrul Syarif (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2016)
In Bangka Belitung Islands Province, squid (Urotheutis chinensis) is a non-fish category fisheries export commodity with a larger amount than other commodities. The high rate of ecosystem damage and high sedimentation of marine areas due to mining activities has caused squid catches in coastal areas to tend to decrease. Based on the research results, the Coral Reef Exploration Team of the University of Bangka Belitung, Tuing waters are a fisheries stronghold in Bangka Regency. This is evidenced by the absence of tin mining activities. The Universitas Bangka Belitung Community Service Program (KKN) in Tuing Hamlet, Mapur Village, Riau Silip Subdistrict, Bangka Regency began in 2014 and 2015 by starting activities to build squid attractor FADs. In 2016, this program was again focused on pioneering Bangka squid cultivation activities with additional programs in the form of developing local potential-based natural tourism potential and educational work programs to increase understanding for the community of the importance of preserving marine ecosystems.marine ecosystem. The results that have been carried out are the collection of squid eggs using a fisherman's net, then incubated in a maintenance aquarium that has been set up using a top filter. The successfully reared squid larvae were then released as a form of restocking activity. natural resources with related stakeholders. The next activity is to increase the potential of coastal tourism (beach) by promoting tourism through website development and building supporting facilities in the form of Saung (simple shelter) provided to all visitors to rest after climbing. can rest after the hike. Another ecotourism development is the coral reef transplantation program by involving the community to increase awareness of the importance of coral reefs in increasing fish biodiversity in Tuing waters. in Tuing waters. In addition to the community, other educational activities were carried out through teaching activities for students of SDN 11 Riau Silip in the classroom by providing exposure related to the topic of marine ecosystems. The educational presentation provided consisted of several topics, namely the introduction of marine ecosystems, the introduction of freshwater and marine biota, the impact of damage to marine ecosystems, and the introduction of the movement to love eating fish.